Empowering Freetown's women farmers. (September 2016) - Cadzow, Hana; Binns, Tony
Abstract: In Freetown, the capital city of Sierra Leone, rapid urbanisation combined with the lingering impacts of the devastating decade long civil war (1991–2002), has left large portions of the population without reliable work or income. One response to this has been an increase in urban and peri-urban agriculture (UPA) which provides participants with employment, income and food security. According to local government estimates, women comprise around 80% of Freetown's UPA community, and many women rely totally on UPA as a livelihood strategy to feed and support their households. This article focuses on the experiences of these women farmers, and in doing so sheds new light on their vital contribution to Freetown's growing UPA community who are not thus far represented in published literature. Globally, women are also underrepresented in UPA literature, and as a result their distinct challenges are not well understood. Reporting on field-based research, this article identifies challenges facing Freetown's women farmers, including land tenure, access to clean water, limited capital for purchasing tools, fertilisers, and pesticides, and difficult relationships with government, NGOs, and other farmers. The manner in which these challenges manifest themselves in relation to women farmers, as distinct from their male counterparts, are identified, and opportunities for Freetown's UPA community to support and empower women farmers will be highlighted. Highlights: UPA is an important livelihood strategy for many women in Freetown, Sierra Leone. Women famers face significant and distinctive challenges as a result of their gender. UPA producers contend with issues such as; land security, poor water quality and access to capital. More support from government and NGOs is needed to improve livelihood outcomes. Women should be empowered to make their own decisions regarding aid allocation.